Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1021/bc0601267
|View full text |Cite
|
Sign up to set email alerts
|

Tat-Functionalized Near-Infrared Emissive Polymersomes for Dendritic Cell Labeling

Abstract: Dendritic cells (DCs) play a pivotal role in both immune tolerance and the initiation of immunological responses. The ability to track DCs in vivo is imperative for the development of DC-based cellular therapies and to advance our understanding of DC function and pathophysiology. Here, we conjugate a cell permeable peptide, Tat, to near-infrared (NIR) emissive polymersomes in order to enable efficient intracellular delivery for future DC tracking with these optical probes. NIR imaging allows quantitative, repe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
133
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 130 publications
(140 citation statements)
references
References 50 publications
6
133
0
Order By: Relevance
“…As previously mentioned, Christian et al demonstrated that the highly cationic HIV-derived TAT peptide, when coupled to NIR-emissive polymersomes, enhances cellular delivery of polymer vesicles to dendritic cells while moderately affecting cell viability [19]. Intracellular uptake of polymersomes was dependent upon their concentration and incubation time in solution; viability was affected by these factors as well [19].…”
Section: Polymersome Surface Modifications For Delivery and Therapymentioning
confidence: 98%
See 4 more Smart Citations
“…As previously mentioned, Christian et al demonstrated that the highly cationic HIV-derived TAT peptide, when coupled to NIR-emissive polymersomes, enhances cellular delivery of polymer vesicles to dendritic cells while moderately affecting cell viability [19]. Intracellular uptake of polymersomes was dependent upon their concentration and incubation time in solution; viability was affected by these factors as well [19].…”
Section: Polymersome Surface Modifications For Delivery and Therapymentioning
confidence: 98%
“…Dendritic cells (DCs) play an important role in the immune response and have shown potent anticancer activity leading to DC-based vaccines research [56]. Current progress in DC-based vaccines has been, however, limited by various factors [56], some of which could be overcome by the development of imaging methods for in vivo DC tracking [19]. Christian et al have demonstrated the ability to label DCs ex vivo with polymersomes encapsulating porphyrinbased NIRFs; the TAT peptide, as will be discussed in greater detail below, was conjugated to these NIR-emissive polymersome to facilitate efficient uptake of polymer vesicles by DCs [19].…”
Section: Diagnostic Applications Of Polymersomesmentioning
confidence: 99%
See 3 more Smart Citations